Identification of isolated bacteria from poultry feces in Beting, Kuala Pilah / Azila Mostafa - Mostafa, Azila (2017)
The chicken (Gallus gallus) is crucial for the industrial production of meat and egg. The bacteria in chicken feces have potential to transmit in human if there were poor hygiene practice. The aim of this study is to isolate and identify the bacteria from chicken feces. The feces sample was collected from the villager’s coop. The samples were collected aseptically and proceed with a serial dilution for subculture process. The pure culture obtained proceeds for gram staining and biochemical test. The bacteria morphology was identified by gram staining and proceeds for biochemical test. The biochemical was MacConkey, eosin-methylene blue, and IMViC test. Two bacteria successfully isolated were Escherichia coli and Salmonella spp.